PENGARUH LATIHAN FINDERS KEEPERS TERHADAP KECEPATAN LARI PADA ATLET ATLETIK KABUPATEN SIAK - Frederika Frentina Frederika Frentina; Ramadi Ramadi '; Ardiah Juita Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: Problem identification results show that there are exercises that can have a significant influence on the running speed on the track and field athletes. The issues raised in this research is, "Is there a finders keepers exercise influence on the speed run on runners Siak? The research hypothesis proposed in this study is that there is finders keepers exercise influence on the speed run on runners Siak. This study aims to determine the effect of exercise finders keepers against runners running speed on the Siak. This study is an experimental research. Research was conducted on Athletes Athletic Siak. The research data obtained and collected through preliminary tests (pretest) before being given treatment and final test (posttest) after being given treatment as much as 16 times with a frequency of 3 times in one week. Data were analyzed using analysis of comparative statistical data. Results of the analysis showed that there are significant finders keepers to speed training run at the Athletics athlete Siak. Based on comparative analysis of statistical data and generate tcount 7.41 ttabel 1,895. Tcount means is smaller than ttabel so that it can be concluded that there are significant finders keepers to speed training run at the Athletics athlete Siak. In other words finders keepers exercise effective influence on the running speed when used minimum of 16 sessions with a frequency of three times a week.Keywords: Finders Keepers Training, Running Speed.